Implementasi Kurikulum 2013 dalam Meningkatkan Prestasi Belajar Siswa - Ahmad Nursobah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2018)
The research is motivated by the development of world science and technology is so rapid, so that Indonesia needs education that can ready the students to compete in the international community in the future. To achieve this goal, then drafted new curriculum is the curriculum of 2013. This study focuses on learning, ranging from design, process, and evaluation in improving student achievement in the curriculum, 2013 in State Islamic Elementary School Ngepoh Tanggunggunung and State Islamic Elementary School Mergayu Bandung Tulungagung. The research is a qualitative research, based on the discussion included descriptive study using multi-site study design. The results of the research are: (1) The design of the learning curriculum in 2013 in improving student achievement that teachers do is to map the first Basic competence to set a theme in the book the teacher, then what will be discussed, translating into an indicator, then create a syllabus and compile into a plan implementation of learning, while different in the two madrassas it is in the process of making learning device. (2) The learning process curriculum 2013 in improving student achievement emphasizes cognitive aspects supported affective, and psychomotor making the learning process more practice than on the material, but it slipped skills to further explore creative skills of learners and maximizing the specific competency. (3) Evaluation of the learning in curriculum 2013 is authentic to improve student achievement using a variety of techniques and instruments ranging from observation, self-assessment, peer assessment, journals, written tests, oral tests, assignments, projects to portfolio performance. It also uses monitoring and mentoring done by parents and teachers use a variety of variations, ranging from book cases rewards and penalties are given to the students, then the evaluation of learning curriculum 2013 in improving student achievement every grade teacher has a book case whose contents of personal services, social services, children's services and difficulty learning to learn, so this book serves to check the attitude during the school day, and will be told to his parents associated with the development of her son at the time of the meeting parents.